Physiological effect of some antioxidant polyphenols on sweet marjoram (Majorana hortensis) plants - ABDALLA EL-MOURSI; IMAN TALAAT; LAILA KAMAL BALBAA (Smujo International, 2012)
Abstract. El-Moursi A, Talaat IM, Balbaa LK. 2012. Physiological effect of some antioxidant polyphenols on sweet marjoram (Majorana hortensis) plants. Nusantara Bioscience 4: 11-15. Two pot experiments were conducted in the screen of the National Research Centre, Dokki, Cairo, Egypt to study the physiological effect of foliar application of some antioxidant polyphenols on growth and chemical constituents of sweet marjoram plants (Majorana hortensis L.). Plants were treated with curcuminoids, cinnamic acid and salicylic acid, each at 5 and 10 mg/L except the control plants. The results indicate that foliar application of curcuminoids increased growth parameters under study. Total sugars were also increased as a result of foliar application of curcuminoids. On the other hand, oil %, oil yield, and nitrogen % were decreased as a result of curcuminoids treatments. Cinnamic acid at 5 mg/L resulted in the tallest plants in most cases. Application of cinnamic acid at 10 mg/L significantly increased oil % and total oil yield/plant. Sugar content followed the same trend. Treatment of sweet marjoram plants with salicylic acid significantly increased oil % and oil yield, especially in plants treated with 10 mg/L SA. Total sugars % and total nitrogen % followed the same trend. The main constituents of the plant essential oil were also markedly affected.